Development of Essential Nursing Competencies for COVID-19 Pandemic: A Case Study of Songkhla Province - Chukumnird, Siriwan; Suwanwaha, Sakkarin; Leecharoen, Phanit; Warahut, Jarunee; Chuakompeng, Apisit; Tejavanija, Naiyanan; Dumrongkullachart, Dararat (Journal of Health Systems Research, 2023)
This emancipatory action research with action research aimed to develop essential nursing competencies for COVID-19 and nursing competency development models for primary, secondary, and tertiary health service units through the case study of Songkhla province where strong government management policy existed in collaboration with stakeholders. A total sample of 53 registered nurses (10 from primary, 31 secondary and 12 tertiary health service units) and 6 physicians were recruited. Research instruments consisted of 1) quantitative data collection tools including the questionnaire of essential nursing competencies for emerging infectious disease COVID-19 and the questionnaire of satisfaction on nursing competency development models for COVID-19. 2) Qualitative data collection tools included the behavioral-based interview, the in-depth interview, and the focus group discussion guidelines. Quantitative data were analyzed using descriptive statistics and qualitative data were analyzed using content analysis. Research results revealed that 1) registered nurses had an overall higher mean score of essential nursing competencies for COVID-19 at each loop of research. Higher mean scores were found on both professional and technical competencies. 2) Nursing competency development model consisted of 3 components including practice guidelines, competency development method, and factors promoting competency development. Practice guidelines consisted of 5 main steps including 1) specification of essential performance competencies; 2) development of monitoring system, support, and empowerment; 3) specification of self-competency development guideline; 4) implementation of the competency development plan; and 5) summarization and report of development result. The competency development method consisted of 6 activities including 1) workshop, 2) on-the-job training, 3) learning from experts, 4) coaching, 5) self-study, and 6) knowledge sharing. Factors promoting competency development included the role of nursing leaders, explicit policy and practice guidelines, and a good attitude towards the profession. Conclusion: research findings could be used as guidelines for the competency development of nursing staff working in primary, secondary and tertiary health service units to have skill and nursing competency for patients with COVID-19 and emerging diseases in the future.